Influence of traits, specific motivation and practical intelligence on exporting entrepreneur's behaviour - Wong, Kam Sun (2020)
Entrepreneurs’ behaviour is proximal to discovering, assessing and taking advantage of opportunities in business. In fact, entrepreneurs and the economic health of a country are closely linked. They provide for organizational survival and are the reasons why new businesses and ventures grow. Recent views that the personality characteristic/traits, and how they affect the behaviour of entrepreneurs has prompted several studies into the entrepreneurs’ behaviour. In this research, data from 319 participating entrepreneurs, each from different SME firms, all members of the Malaysian Plastic Manufacturing Association were obtained and analysed. Nineteen entrepreneurs participated in three qualitative focus group interviews to develop the measure items for each of the eight constructs. Three hundred entrepreneurs participated in the quantitative survey using the structured questionnaire generated from the qualitative phase. Comparison between SPSS SEM-AMOS (Statistical Package for the Social Sciences 20.0, and the Structural Equation Modelling-Analysis of Moments Structures 20.0) and the Smart-PLS 2.0 revealed a better match of all the eight assumptions of this research with the former software package. Thus, the analysis was performed using the SEM-AMOS 20.0 package. Results of this study showed tenacity and resourcefulness to have significant direct effect on situationally specific motivation (SSM), which was in turn found to have significant direct effect on both exporting entrepreneur’s behaviour, and practical intelligent. Passion has no significant direct effect on SSM but on exporting entrepreneur’s behaviour. The three factors of the SSM, namely communicated vision, goal-setting, and self-efficacy unidimensionally mediated the effects of both tenacity and resourcefulness. Meanwhile, practical intelligence has both significant direct effect on exporting entrepreneur’s behaviour and significant partial mediation of the effects of SSM. This SEM model represented 68% of the variance in total performance. These empirical findings imply the personality traits of passion, tenacity and resourcefulness have strong influence on the entrepreneur’s behaviour as the criterion for success of the SME exporting, and when these traits acted in concert with specific motivation, and practical intelligence, produces the winning combination for an entrepreneur’s culture of performance for the SME. This critical success factor for sustainable exporting has strong management implication to the government to develop special coaching and training for all SMEs in the country.